2019
DOI: 10.1038/s41598-019-54932-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Mindfulness-Based Stress Reduction in Cardiac Patients Eligible for Cardiac Rehabilitation

Abstract: Currently, exercise-based cardiac rehabilitation (CR) is the only recommended secondary prevention strategy for cardiac patients that attempts to tackle stress and psychosocial wellbeing, but it is under-utilized and lacks a comprehensive curriculum for this purpose; hence there is a critical gap to address psychosocial needs of cardiac patients after an event. Mindfulness-based stress reduction (MBSR) has shown benefits in the general population but its role in cardiac patients is not clear. We conducted a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(36 reference statements)
0
25
0
Order By: Relevance
“… 15 Mindfulness, meditation, yoga, and other relaxation techniques have also been suggested as ways to reduce stress. 30 , 31 , 32 A meta-analysis 31 of 42 studies that included yoga and mindfulness-based stress reduction techniques reported associations with lower evening and waking cortisol levels, lower systolic blood pressure, resting heart rate, heart rate variability, fasting blood glucose, cholesterol, and low-density lipoprotein-cholesterol compared with active controls.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Mindfulness, meditation, yoga, and other relaxation techniques have also been suggested as ways to reduce stress. 30 , 31 , 32 A meta-analysis 31 of 42 studies that included yoga and mindfulness-based stress reduction techniques reported associations with lower evening and waking cortisol levels, lower systolic blood pressure, resting heart rate, heart rate variability, fasting blood glucose, cholesterol, and low-density lipoprotein-cholesterol compared with active controls.…”
Section: Discussionmentioning
confidence: 99%
“…In an RCT involving patients undergoing cardiac rehabilitation following acute coronary events, 3 months of yoga practice showed no difference in FBG compared to the usual care ( n = 60) [ 34 ]. In another study for cardiac patients, no change was found in HbA1c level after 8 weeks of MBSR program ( n = 47) [ 35 ].…”
Section: Potential Effects Of Mbi On Glycemic Controlmentioning
confidence: 99%
“…MBIs have also been found to improve stress, depressed mood, and sleep quality [ 55 - 57 ], which are all intertwined with chronic pain. Moreover, MBIs are emerging as promising approaches for mitigating heart disease and promoting cardiac rehabilitation [ 58 - 60 ]. Specifically, MBCT—which combines mindfulness strategies and cognitive therapy—is one of the most widely researched MBIs and may be uniquely suited for pain management given its potential effect on pain-related psychological factors such as catastrophic thinking and pain acceptance [ 21 , 61 - 65 ].…”
Section: Introductionmentioning
confidence: 99%